A Comparison of Regulatory Oversight of Loan Interest Rates on Peer-to-Peer Lending Platforms in Indonesia and the United States - Kurniayudha, Wikian Fadam; Setianingrum, Reni Budi (Universitas Muhammadiyah Yogyakarta, 2026)
The rapid growth of financial technology, particularly peer-to-peer (P2P) lending, has expanded public access to financing but has also raised concerns regarding high and insufficiently transparent loan interest rates, which may increase default risks and weaken consumer protection. This study aims to analyze the supervision of P2P lending interest rates in Indonesia and compare it with the regulatory framework in the United States (US) to identify a more effective and equitable regulatory model. This research employs a normative legal method using statutory and comparative law approaches through a literature review of relevant legislation, legal doctrines, and scholarly works. The findings indicate that Indonesia has established a regulatory framework through the authority of financial regulators to set maximum interest rate limits. However, the implementation of supervision and transparency still faces several challenges. In contrast, the US regulates lending interest rates through mandatory disclosure of the Annual Percentage Rate (APR) and interest rate limitations under state-level usury laws. The study concludes that strengthening interest rate supervision, enhancing transparency, and refining regulatory policies are necessary to improve consumer protection and reduce default risks in Indonesia’s P2P lending industry.